General geology and the prediction of limestone geohazard using electrical resistivity imaging (eri) at Gua Madu, Gua Musang, Kelantan. - Abdul Hakim Yahaya (2017)
This study is about the general geology and prediction of limestone geohazard by using electrical resistivity imaging at Gua Madu, Gua Musang, Kelantan. The purpose of this study is to enhance the geological map of study area to scale 1:25000 and to assess limestone geohazard of the study area. The geological map is enhanced by geological mapping , field observation and sampling of rocks. The rocks sample is cut into thin section for petrography analysis. Reading of joints in strike and dip is taken for structural analysis. To assess the limestone geohazard of the study area, electrical resistivity imaging (ERI) method is selected. By using the ERI method, subsurface voids are found at the target area. There are three electrical resistivity profiles labelled P1, P2 and P3. P1 and P2 shows that these area is very stable due to the presence of massive limestone underground and high resistivity value detected. P3 shows that the risk of potential limestone geohazard to occur is high based on the undergroundwater found and low resistivity value in the area. The overall results from this study indicate that the study area is stable and the risk of potential limestone geohazard to occur is low.